Peningkatan Kontrol Sosial Masyarakat Dalam Upaya Pencegahan Penyalahgunaan NAPZA - Putra Pratama Saputra (Society, 2017)
The drug abuse problem that occured in society these days is very alarming. The existence of the perpetrator and the activity of drug abuse has become a custom of the community. However, permissiveness shown as if the people let these problems occur. The existence of stakeholders is expected to have a positive impact, so that the functions of society can work well, especially in the prevention of drug abuse. The improvement of society social control is an effort to prevent drug abuse. The purpose of this research is to improve the society social control as away to prevent drug abuse. The method used in this research is a qualitative research method with action research. The Place of research conducted in RW 18 Sadang Serang Village, Coblong Sub-district, Bandung with a number of main informants and supporting informant were 6 people as many as 3 people. The intervention is done through several activities, namely the Counseling and Socialization, Social Campaign, and Forming Local Organization “Pemuda Anti NAPZA”. The results showed an increase in society social control is an effort to prevent drug abuse in RW 18 Sadang Serang Village. Final model has been enhanced tends to be more effective in addressing the problem of drug abuse which is occured.